Using Serum Levels of Calcium, Magnesium, and Calcium/Magnesium Ratio to Predict Preeclampsia - Aseel Rifat; Taghreed Al-Rawi (Al-Anbar Medical Journal)
Background: Preeclampsia (PE) is a systemic disorder of pregnancy that is associated with significant perinatal morbidity and mortality. Calcium (Ca) and magnesium (Mg) play a  pivotal role in regulating the contractility and tone of the cardiac and vascular muscle fibers.Objectives: To assess the role of serum levels of Ca, Mg and Ca/Mg ratio as predictors of PE severity.Materials and methods: A prospective cohort study was conducted that included 200 pregnant women who attended three prenatal checkups at 11, 24, and 35 weeks of gestation. Serum Ca and Mg levels were measured at each visit.Results: At the 11th week, the mean serum Ca level, Mg level, and Ca/Mg ratio were 9.09 ± 0.60 mg/dl, 2.92 ± 0.72 mg/dl and 3.28 ± 0.76, respectively. At the 24th week, women with early PE had the lowest mean serum Ca (7.94 ± 0.64 mg/dl) as compared to those without the health problem (9.12 ± 0.60 mg/dl). At the 35th week, preeclamptic women had significantly reduced serum Ca, Mg, and Ca/Mg ratio compared to non-preeclamptic women. The lowest mean serum levels of Ca, Mg, and Ca/Mg ratio were found in severe compared to mild PE (P-value < 0.05). At the 11th week, the cutoff values of 8.18 mg/dl for serum Ca, 2.04 mg/dl for Mg, and 3.09 for Ca/Mg ratio were valuable for predicting the severity of PE at the 35th week of pregnancy with 100% sensitivity and a specificity of 87%, 91% and 81%, respectively.Conclusion: The serum Ca, Mg, and the Ca/Mg ratio, measured at the 11th  week of gestation, were critical predictors of severe PE at the 35th  week.